Characterisation of nickel electrodes by electrochemical impedance spectroscopy - Ray T. Barton (1995)
The thesis describes an electrochemical investigation of different types of nickel electrode used in nickel-cadmium cells, which are available commercially or currently under development. Impedance spectroscopy has been used to determine the electrochemical characteristics of these electrodes. The electrochemistry of the nickel electrodes was modelled by the electrical analogue method. Allowance was made within the model for porosity and adsorption effects. Component values were initially estimated by graphical techniques and the computer fitting procedure was then completed by an iterative process to provide kinetic parameters which were used to compare and contrast the characteristics of the nickel sintered, pocket and plastic bonded electrodes. The technological target of this work was establish a possible method by which the residual capacity remaining within nickel-cadmium cells could be determined. The kinetic parameters generated by the electrical analogue technique have provided data on which to base a measurement for the prediction of the state of charge in nickel-cadmium cells.